Revisiting the pharmacodynamic uroselectivity of a1-adrenergic receptor antagonists - Quaresma, Bruna Maria Castro Salomão; Pimenta, Amanda Reis; Santos da Silva, Anne Caroline; Pupo, André Sampaio [UNESP]; Romeiro, Luiz Antonio S.; Silva, Claudia Lucia Martins; Noël, François (Elsevier, 2019)
a1-Adrenoceptor (AR) antagonists are widely used for the relief of urinary retention secondary to benign prostatic hyperplasia (BPH). While the five Food and Drug Administration–approved a1-AR antagonists (terazosin, doxazosin, alfuzosin, tamsulosin, and silodosin) share similar efficacy, they differ in tolerability, with reports of ejaculatory dysfunction. The aim of the present work was to revisit their a1-AR subtype selectivity as well as of LDT5 (1-(2-methoxyphenyl)-4-[2-(3,4-dimethox-yphenyl) ethyl]piperazine monohydrochloride), a compound previously described as a multitarget antagonist of a1A-/a1D-AR and 5-HT1A receptors, and to estimate their affinity for D2, D3, and 5-HT1A receptors, which are putatively involved in ejaculatory dysfunction. Competition binding assays were performed with native (D2, 5-HT1A) or transfected (human a1A-, a1B-, a1Dt-AR, and D3) receptors for determination of the drug’s affinities. Tamsulosin and silodosin have the highest affinities for a1A-AR, but only silodosin is clearly a selective a1A-AR antagonist, with Ki ratios of 25.3 and 50.2 for the a1D- and a1B-AR, respectively. Tamsulosin, silodosin, and LDT5 (but not terazosin, doxazosin, and alfuzosin) have high affinity for the 5-HT1A receptor (Ki around 5–10 nM), behaving as antagonists. We conclude that the uroselectivity of tamsulosin is not explained by its too-low selectivity for the a1A- versus a1B-AR, and that its affinity for D2 and D3 receptors is probably too low for explaining the ejaculatory dysfunction reported for this drug. Present data also support the design of “better-than-LDT5” new multitarget lead compounds with pharmacokinetic selectivity based on poor brain penetration and that could prevent hyperplastic cell proliferation and BPH progression.